2013
DOI: 10.1093/bib/bbt035
|View full text |Cite
|
Sign up to set email alerts
|

Systems pharmacology in drug discovery and therapeutic insight for herbal medicines

Abstract: Systems pharmacology is an emerging field that integrates systems biology and pharmacology to advance the process of drug discovery, development and the understanding of therapeutic mechanisms. The aim of the present work is to highlight the role that the systems pharmacology plays across the traditional herbal medicines discipline, which is exemplified by a case study of botanical drugs applied in the treatment of depression. First, based on critically examined pharmacology and clinical knowledge, we propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
132
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(132 citation statements)
references
References 130 publications
0
132
0
Order By: Relevance
“…Due to the complexity of chemical composition, only using a single index or a simple superposition method could not be feasible to unveil the multi-herb synergistic characteristics of TCM (Jin et al, 2016). Thus, recently, researchers tried to use knockout/knockin chromatography, bioactive equivalence oriented feedback screening method (Song et al, 2016) and system pharmacology strategy (Huang et al, 2014; Zhang W.J. et al, 2016) to recognize the bioactive equivalent combinatorial components (BECCs) or the most effective chemicals in one formula.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of chemical composition, only using a single index or a simple superposition method could not be feasible to unveil the multi-herb synergistic characteristics of TCM (Jin et al, 2016). Thus, recently, researchers tried to use knockout/knockin chromatography, bioactive equivalence oriented feedback screening method (Song et al, 2016) and system pharmacology strategy (Huang et al, 2014; Zhang W.J. et al, 2016) to recognize the bioactive equivalent combinatorial components (BECCs) or the most effective chemicals in one formula.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the underlying mechanism of such synergistic effect, it is important to search the knowledge about the therapeutic targets of drugs. Network pharmacology has undergone a rapid development in recent years and emerged as an invaluable tool for describing and analyzing complex systems in pharmacology studies 78, 79 . In this section, the network approach was applied to analyze the active compounds and their targets for the modified Yimusake formula from a network point of view.…”
Section: Resultsmentioning
confidence: 99%
“…Current studies have indicated that two or more herbs interact with multiple targets simultaneously at reasonably close affinities in the biological network and then the biological system would attain new equilibrium in order to reduce the harmful impact26. In such an interlinked network, it would have some effects on the body through this network when a drug targets at a protein.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, these methods only focus on the prediction of drug-target or drug-disease interactions individually, they ignored the concept that TCM emerged and were considered as a holistic view of the human being which included the integration and dissection of pharmacokinetics profiles, pharmacological features and underlying synergistic mechanisms of action associated with drugs, as well as the investigation of various complex relationships, such as drug-target interactions, drug-disease connections, target-disease associations, drug-pathway connections and from molecular to system level. In comparison with these approaches, systems pharmacology is likely to be a comprehensive method in providing a wealth of information for integrated multi-scale analysis of synergistic mechanisms of multi-component drugs and interrelationships of complex networks by using both computational and experiments techniques242526. With this understanding, the application of systems pharmacology in herb pairs may effectively and systematically help to elucidate the synergistic mechanism of drug combinations, including the build-up of pharmacological networks, so as to promote the discovery of new therapeutic indication of existing drugs and potential synergistic drug combinations.…”
mentioning
confidence: 99%